2015
DOI: 10.1186/s11671-015-0857-8
|View full text |Cite
|
Sign up to set email alerts
|

Thin film encapsulation for organic light-emitting diodes using inorganic/organic hybrid layers by atomic layer deposition

Abstract: A hybrid nanolaminates consisting of Al2O3/ZrO2/alucone (aluminum alkoxides with carbon-containing backbones) grown by atomic layer deposition (ALD) were reported for an encapsulation of organic light-emitting diodes (OLEDs). The electrical Ca test in this study was designed to measure the water vapor transmission rate (WVTR) of nanolaminates. We found that moisture barrier performance was improved with the increasing of the number of dyads (Al2O3/ZrO2/alucone) and the WVTR reached 8.5 × 10−5 g/m2/day at 25°C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 21 publications
0
30
0
Order By: Relevance
“…4. It was found that the water barrier properties were enhanced with the increase of the dyad ( 19 Commercially, in order to assure the minimum lifetime of most OLEDs at least for 10000 h, the WVTR should be less than 10 À6 g per m 2 per day. 2 Al 2 O 3 /alucone laminates with more number of dyads and thickness should be used.…”
Section: Optimization Of Al 2 O 3 /Alucone Structures and Their Barrimentioning
confidence: 99%
See 1 more Smart Citation
“…4. It was found that the water barrier properties were enhanced with the increase of the dyad ( 19 Commercially, in order to assure the minimum lifetime of most OLEDs at least for 10000 h, the WVTR should be less than 10 À6 g per m 2 per day. 2 Al 2 O 3 /alucone laminates with more number of dyads and thickness should be used.…”
Section: Optimization Of Al 2 O 3 /Alucone Structures and Their Barrimentioning
confidence: 99%
“…However, the structure, e.g., the individual layer thickness and the number of stacks, is remained for further improvement. [18][19][20] In this work, Al 2 O 3 /alucone with maximum thickness of 102.5 nm have been fabricated using ALD/MLD under a low temperature of 90 C. The optical and moisture barrier performances were then investigated with respect to the individual layer thickness and the number of stacks. Finally, the barrier performance and three-dimensional conformality of Al 2 O 3 /alucone lms were conrmed as top barrier of OLED devices with uneven pixel dened layer (PDL).…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic encapsulation materials, e.g., commercialized Al 2 O 3 , SiO x , and SiN x , show superior protection from moisture. However, they suffer from both factors of poor flexibility and pinhole defects in the layer surface . At present, inorganic/organic hybrid has been considered as one of the most effective barrier technologies of flexible OLEDs.…”
Section: Flexible Oledsmentioning
confidence: 99%
“…At present, inorganic/organic hybrid has been considered as one of the most effective barrier technologies of flexible OLEDs. Typical examples include ZnO/parylene C, SiN–acrylate–SiN, Al 2 O 3 /ZrO 2 /alucone, zinc‐tin‐oxide (ZTO)/ORMOCER/ZTO, polymer/graphite nanocomposites, etc. Specifically, a water vapor transmission rate (WVTR) of less than 10 −6 g m −2 d −1 and an oxygen transmission rate (OTR) as low as 10 −5 cm 3 m −2 d −1 should be achieved to develop sufficient barriers for OLEDs…”
Section: Flexible Oledsmentioning
confidence: 99%
“…The DBR ZrO 2 /zircone films were deposited in the Beneq TFS-200 ALD reactor, which has been explained in another work [21]. Firstly, the sonication was conducted to clean the glass substrate, which was then put in detergent solution as well as deionized water in succession and then treated by UV ozone.…”
Section: Ald Zro 2 /Zircone Dbr Structurementioning
confidence: 99%